Navigating Excellence: Exploring Education Systems of Singapore & Republic of South Korea; Insights for Pakistan’s Educational Landscape - Tabassum Shairwani; Syeda Aqsa Bint a Zafar; Zul Ul Ane Fatima (Indus Journal of Social Sciences, 2025)
This concept paper aims to study the education systems of Singapore & Republic of Korea (ROK) focusing on the factors that have led to the phenomenal success of these countries in the field of education. Using a comparative framework, the study highlights cultural values, government policies, and systemic structures that have shaped the educational landscapes of these nations. This study maintains that the culture, ideals, government policies and work ethics of the people of these two countries have led to their current esteemed status among the comity of the nations in the field of education. Pakistan’s education system faces significant challenges, including low investment in education, weak governance, and inadequate teacher training as well as inconsistent and inefficient policy implementation. This paper provides strategic recommendations for Pakistan, drawing on the successful policies of Singapore and Republic of South Korea to improve its education system. The paper highlights the importance of adapting Pakistan’s education system to meet the needs and demands of changing times in accordance with global trends and most importantly prioritizing education for human capital development and creating a workforce that is ready to tackle the challenges in an increasingly competitive world.